2004
DOI: 10.1007/s10517-005-0138-0
|View full text |Cite
|
Sign up to set email alerts
|

Morphological manifestations of heart remodeling in anthracycline-induced dilated cardiomyopathy

Abstract: The morphogenesis of anthracycline-induced dilated cardiomyopathy was studied after single sublethal dose of doxorubicin. Cardiomyocyte depopulation (up to 27%) and decrease in their regeneratory plastic reactions were the main mechanisms of cardiac failure development after anthracycline (doxorubicin) treatment, determining the type of heart remodeling by the dilatation variant. Cardiomyocyte elimination and atrophy during the development of anthracycline-induced regeneratory plastic cardiac insufficiency wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The myoblastic cell line H9c2 (Kimes and Brandt 1976) is a well-characterized in vitro system used to study Dox-induced biochemical changes and the protective effect of a wide number of compounds (Chua et al 2006;L'Ecuyer et al 2006;Spallarossa et al 2004;Wattanapitayakul et al 2005). For example, a recent study demonstrated that Dox treatment leads to hypertrophy of H9c2 cells (Merten et al 2006), similar to what has been observed in adult cardiomyocytes during the development of the Dox-induced cardiomyopathy (Lushnikova et al 2004). Despite some work conducted on the biochemical alterations of H9c2 cells induced by Dox, the evaluation and characterization of morphological modifications has not been extensively studied.…”
mentioning
confidence: 86%
“…The myoblastic cell line H9c2 (Kimes and Brandt 1976) is a well-characterized in vitro system used to study Dox-induced biochemical changes and the protective effect of a wide number of compounds (Chua et al 2006;L'Ecuyer et al 2006;Spallarossa et al 2004;Wattanapitayakul et al 2005). For example, a recent study demonstrated that Dox treatment leads to hypertrophy of H9c2 cells (Merten et al 2006), similar to what has been observed in adult cardiomyocytes during the development of the Dox-induced cardiomyopathy (Lushnikova et al 2004). Despite some work conducted on the biochemical alterations of H9c2 cells induced by Dox, the evaluation and characterization of morphological modifications has not been extensively studied.…”
mentioning
confidence: 86%
“…Pathological studies on experimental animal models and human endomyocardial biopsies have shown that anthracycline-induced cardiomyopathy is characterized by histological alterations consisting in multiple areas of interstitial fibrosis associated with the presence of cardiomyocytes with vacuolar degeneration or compensatory hypertrophy. Necrotic cardiomyocytes with cellular infiltration, stromal edema with myocardial fibers dissociation, and the presence of polymorphonuclear cells can also be observed [68]. …”
Section: Introductionmentioning
confidence: 99%
“…Experimental study of structural mechanisms of dilated cardiomyopathy (at the tissue, cellular, and intracellular levels) showed that heart remodeling by the dilatation variant is caused by the development of regeneratory and plastic insufficiency of cardiomyocytes (CMC), followed by apoptosis and appreciable loss of these cells [1,4]. Diffuse CMC apoptosis can cause a 10-30% decrease in their total count, which serves as the triggering mechanism for dilatation remodeling [2,6,7,12].…”
mentioning
confidence: 99%